Evaluation of Classical Cesarean Delivery Outcomes [20K]. (May 2016) - Kawakita, Tetsuya; Reddy, Uma M.; Landy, Helain; Grantz, Katherine; Desale, Sameer; Iqbal, Sara
Abstract : INTRODUCTION: To compare maternal outcomes for classical cesarean delivery (CCD) with low transverse cesarean delivery (LTCD) early preterm. METHODS: We conducted a multi-hospital retrospective cohort study of women undergoing cesarean delivery (CD) at 23–31 weeks between 2005 and 2014. Intraoperative outcomes (incision-delivery time [ID-time], total operative time [TO-time], and estimated blood loss [EBL]) and composite maternal outcome (postpartum hemorrhage, transfusion, endometritis, sepsis, wound infection, deep venous thrombosis/pulmonary embolism, hysterectomy, pulmonary edema, and intensive care unit [ICU] admission) were compared between CCD and LTCD. Outcomes were calculated using multivariable logistic regression models yielding adjusted odds ratios (aOR) with 95% CI and adjusted P values controlling for maternal characteristics, emergency CD, and comorbidities. Analyses were stratified by gestational age (GA) groups (23–27 and 28–31 weeks) as well as primary versus repeat CD. RESULTS: Of 902 women meeting inclusion criteria, 221 (64%) and 82 (16%) underwent CCD at 23–27 and 28–31 weeks, respectively. For primacy CDs, no difference was seen in ID-times regardless of GA. For repeat CDs, CCD was associated with longer ID-times regardless of GA ( P <.05 for all). Primary and repeat CCD were associated with longer TO-times regardless of GA ( P <.01 for all). At 28–31 weeks, CCD was associated with increased risk of transfusion (aOR=3.06; 95% CI=1.39–6.75), ICU admission (aOR=5.42; 95% CI=1.39–21.06), and composite maternal outcome (aOR=2.23; 95% CI=1.27–3.91); no increased risk was seen for CCD at 23–27 weeks. CONCLUSION: CCD at 28–31 weeks was associated with increased maternal complications. CCD did not enhance faster ID-time and therefore CCD solely for facilitating more rapid delivery is not indicated.